2016
DOI: 10.3390/sports4040049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbohydrate Intake on Maximal Power Output and Cognitive Performances

Abstract: The present study aimed to assess the beneficial effect of acute carbohydrate (7% CHO) intake on muscular and cognitive performances. Seventeen high levels athletes in explosive sports (fencing and squash) participated in a randomized, double-blind study consisting in series of 6 sprints (5s) with a passive recovery (25s) followed by 15 min submaximal cycling after either maltodextrine and fructose (CHO) or placebo (Pl) intake. Cognitive performances were assessed before and after sprint exercise using a simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 49 publications
1
20
1
Order By: Relevance
“…At first glance, the results of the current investigation appear to contrast with previous studies, which have concluded that CHO supplementation improves SIE performance [18][19][20]. However, there are aspects of each of these three studies which can be critiqued.…”
Section: Evidence For Performance Effects Of Cho Ingestion and Siecontrasting
confidence: 92%
See 4 more Smart Citations
“…At first glance, the results of the current investigation appear to contrast with previous studies, which have concluded that CHO supplementation improves SIE performance [18][19][20]. However, there are aspects of each of these three studies which can be critiqued.…”
Section: Evidence For Performance Effects Of Cho Ingestion and Siecontrasting
confidence: 92%
“…In the current study, both peak (PPO) and mean power outputs (MPO) systematically declined with each interval, relative to the previous interval, which is in agreement with observations from previous SIE studies [18,20,24,25,28]. Bogdanis et al [25] demonstrated that following performance of a second consecutive 30 s sprint with either 1.5, 3 or 6 min of passive recovery, neither of these recovery periods were sufficient to maintain PPO or MPO compared to the first sprint.…”
Section: Potential Impact Of Cho On Performancesupporting
confidence: 92%
See 3 more Smart Citations